Ionization energy losses of cosmic rays in graphene nanostructures calculation - Tukhfatullin, T.A.; Grichshenko В.Ф.; Ismailov Д.В.; Gordienko Г.И.; Nakysbekov Ж.Т.; Tronin Б.А.; Bellucci С. (Recent Contributions to Physics, 2024)
Currently, in the Republic of Kazakhstan, within the framework of the strategic directions of the space industry, fundamental and applied scientific space research is being developed, and practical problems are being solved using space technology. In these studies, special attention is paid to the reliability of on-board equipment under the complex influence of outer space factors. In the development and design of such work as docking and assembly of elements of orbital stations, remote control of automatic interplanetary stations and many others, mathematical and computer modeling is used, which is a highly effective and relatively low-cost method. The purpose of this work is to study the dependence of the energy losses of relativistic ions of cosmic radiation when particles pass through graphene nanostructures in order to predict their radiation resistance when exposed to cosmic radiation particles. The simulation of the trajectories and energy losses of relativistic ions during passing through graphite crystals were performed. Numerical values ​​of the critical channeling angles in a graphite crystal are obtained. It is shown that ion energy losses do not depend on the point of entry of the ion into the crystal and increase sharply with decreasing energy in the energy range less than 1000 MeV/nucleon.